SERANGAN HAMA ULAT KROP (Crocidolomia pavonana F.) PADA TANAMAN KUBIS (Brassica oleracea var. capitata L.) DI KELURAHAN KAKASKASEN II, KECAMATAN TOMOHON UTARA, KOTA TOMOHON - Rany Badjo; Caroulus S. Rante; Elisabeth R.M. Meray; Berty H. Assa (Universitas Sam Ratulangi, 2015)
ABSTRACT The study aimed to find out the attacks of caterpillar pests on cabbage crop in the Village of Kakaskasen II, District of North Tomohon, Tomohon. Research has been conducted on cabbage in the Village of Kakaskasen II, Tomohon. The study lasted four months, which began in March 2015 until July 2015. The study was conducted by surveys using sampling methods of purporsive sampling. Cabbage plants showing symptoms were observed. Cabbage plants with symptoms counted as attacked by caterpillars, although no larvae found. Data were observed in this study were (i) symptoms of attacks by caterpillar pest on the crop, (ii) the number of part of the plant showing symptoms and no symptoms, (iii) cabbage crop weight. Parts of plants that were observed for the caterpillar attack were the leaf, the crop, the crop and leave, and the growing point. The results showed that the percentage of attacks of caterpillar crop of C. pavonana in Village of Kakaskasen II reached 48.83 percent. The crop part showed the highest pecent of attack, which was 16.84 percent, followed by the crop and leave parts of 15.24 percent, and then the growing point parts by 13.61 percent, and the lowest was 3.14 percent was found on the leaf part. The average weight of cabbage crop are attacked by pests caterpillar crop, C. pavonana lower (1.44 kg) compared to cabbage crop is not affected (3.34 kg ). Keywords: Crocidolomia pavonana, Brassica oleracea var. capitata L., Tomohon.